SISTEM INFORMASI PENGADAAN DAN MONITORING INVENTARIS PADA PT. PERSADA LAMPUNG RAYA BERBASIS WEB - Akhmad Ikhwan; Wayan Sudarme (Jurnal Multimedia dan Android (JMA), 2023)
AbstractÂ To deal with traffic on this unfriendly road, consumers prefer vehicles that are comfortable and safe to use in various changing conditions and weather. So, not a few people choose cars as a means of transportation that can answer their needs. Promotional activities This is certainly used by all car dealers who do not want to run out of sense so that the cars sold are sold out. But this must be balanced with a qualified supply of goods when a massive promotion or promo is carried out to make customers interested. Do not let mistakes occur in promote the product, which should be out of stock, but still promoted. Of course, there must be a note or system that specifically handles this so that it runs smoothly.Keywords: system information product